The Role of Jaka Laras Kenthongan Arts in Shaping Social Interaction among Nahdliyyin Communities in Sinduraja Village - Akhsani Alfania (Journal of Nahdlatul Ulama Studies, 2023)
Modernization and the growing preference for popular-culture entertainment often undermine the sustainability of traditional arts; however, in Sinduraja Village (Kaligondang, Purbalingga), kenthongan performed by the Jaka Laras group has persisted and functions as a social meeting space for local residents. This study addresses two main questions: (1) how the existence of Jaka Laras kenthongan is maintained in Sinduraja Village and (2) how community members perceive the influence of this existence on social interaction. Employing a qualitative case-study approach, data were collected through observation, in-depth interviews with the founder, community leaders, performers, and village government representatives, and documentation. Credibility was strengthened through triangulation, and analysis followed an interactive model (data collection, data reduction, data display, and conclusion drawing). The findings indicate that Jaka Laras’s continuity is sustained through intergenerational transmission, regular rehearsals and performances, and social support from residents and village authorities, accompanied by selective adaptation in performance packaging without altering the tradition’s core values. At the same time, residents perceive Jaka Laras as increasing the frequency of gatherings, discussions, and social bonding, while reducing tendencies toward individualism, thereby strengthening community cohesion and social capital. The study concludes that Jaka Laras kenthongan not only endures as a traditional art form but also effectively shapes local social relations. Recommendations include strengthening youth–child regeneration programs, enhancing village facilitation (rehearsal spaces and cultural agendas), and conducting comparative studies across villages or kenthongan groups to map variations in preservation strategies and their social impacts across different socio-cultural contexts